2013
DOI: 10.4012/dmj.2013-070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermediate ceramics and firing temperature on bond strength between tetragonal zirconia polycrystal and veneering ceramics

Abstract: The purpose of the present study was to investigate the influence of the intermediate ceramics and firing temperature on bond strength between tetragonal zirconia polycrystal (TZP) and its intermediate ceramics. Two types of intermediate ceramics, defined as a ceramics placed between the TZP and its veneering ceramics, were used; one including high-strength lithium-disilicate (EP) or feldspathic liner porcelain (SB). The firing temperature of the intermediate ceramics was set at 930°C, 945°C or 960°C. Shear bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…In this study, the veneering porcelain, the liner and the connector had compatible CTE values with that of the Y-TZP core. The intermediate ceramic layers such as liner or connector may increase the wettability of the core surface as well as compensate for the discrepancy in the thermal expansion behavior between the veneer and the substrate [17,19,20]. The wetting property is determined by the composition of the adhesive material, the morphology of the zirconia surface and the surface energy of the core [21].…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the veneering porcelain, the liner and the connector had compatible CTE values with that of the Y-TZP core. The intermediate ceramic layers such as liner or connector may increase the wettability of the core surface as well as compensate for the discrepancy in the thermal expansion behavior between the veneer and the substrate [17,19,20]. The wetting property is determined by the composition of the adhesive material, the morphology of the zirconia surface and the surface energy of the core [21].…”
Section: Discussionmentioning
confidence: 98%
“…The mean conventional SBS values reported for zirconia-porcelain combinations in the literature covered a range of 17-55 MPa 4,16,[37][38][39][40][41][42][43][44] . However, the mean ME-SBS values obtained in the present study ranged from 7-10 MPa, which are much lower than those for conventional SBS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, zirconia cores for crown frameworks still require application of veneering ceramics, typically with specialized porcelain, to achieve optimum aesthetics 1) . Certain studies have reported the clinical failures of veneered zirconia FPDs due to veneer debonding, chipping, or fracture defects which were reported to be around 15% after 2-5 years 1,[5][6][7] . The adhesion between the zirconia substrate and veneer ceramics (v-c) is based on various factors such as chemical bonding, mechanical interlocking, wetting properties, interfacial stress, thermal expansion mismatch and glass transition temperature 1,8) .…”
Section: Introductionmentioning
confidence: 99%